Soybean domestication and lead stress on plant–herbivore–parasitoid interactions - Yating Liu; Luhan Li; Shangyang Li; Jiahao Xu; Zhaoyi Feng; Zhe Wang; Liya Zeng; Xiaohong Li (Biological Control)
Plant domestication and soil heavy metal pollution alter plant–insect interactions and influence bottom-up and top-down effects. However, their combined effect on plants, herbivores, and parasitoids remains unclear. Here, we selected three soybean genotypes, namely wild N23312, landrace N28386, and cultivated Xiangdou 33, from the same region and examined the combined effects of soybean genotype and lead (Pb) on soybeans, the herbivore Spodoptera litura, and its parasitoid Meteorus pulchricornis. The effects of soybean genotype, Pb, and their combination significantly affected soybean nutrition and defense compounds, as well as the fitness of S. litura and M. pulchricornis, along with parasitoid host selection. Pb stress decreased soybean soluble protein and sugar contents, increased trypsin inhibitor and leaf Pb contents, and extended the developmental period of S. litura while simultaneously reducing its survival and body weight. Pb stress reduced M. pulchricornis cocoon weight, adult longevity, hind tibial length, and offspring fecundity and extended the parasitoid developmental period. Pb stress primed soybean plant defenses and the effects varied significantly among soybean genotypes. The wild genotype was affected the most, followed by the landrace and cultivated genotypes, which negatively affected S. litura and M. pulchricornis. Meteorus pulchricornis exhibited a preference for S. litura larvae in Pb-stressed soybeans, with preference ranking from wild to landrace to cultivated genotypes. The findings enhance our understanding of the ecological mechanisms underlying plant–insect interactions under domestication and environmental stress.